Combustion of Al nanoparticles coated with ethanol/ether molecules by non-equilibrium molecular dynamics simulations. (March 2020) - Liu, Junpeng; Liu, Pingan; Wang, Mengjun; Wang, Wenchao; Lv, Fangwei; Sun, Ruochen; Yang, Yanxi
Highlights: Coating Al nanoparticle (ANP) with organic small molecular materials: ethanol and ether as a novel clean energy. The relationship between ANPs and their coating layer during the ignition and combustion stages is firstly studied. Thermodynamic performance improved by organic layer from the ignition to combustion period is studied detailly. Properties of two organic coating layer including structure and chemical reactivity aspects are discussed detailly. Abstract: Al nano-particle (ANP) is vulnerable to external oxidation environment due to its high reactivity. To overcome such drawback, we coat ANPs with organic materials: ethanol and diethyl ether. Comparative discussions are raised from the coating to combustion process between bare ANP and other ANPs with different organic coating layers. Our results show the structure of organic coating layer is different for ethanol and diethyl ether molecules. ANPs prefer adsorbing ethanol molecules for its relatively simple structure and molecular polarity. In the heating stage, the presence of organic coating layers is beneficial for ANPs to attract external oxygen molecules, but the content of active Al atoms is reduced. The combustion stage can be divided into four stages according to the rate of temperature change. ANPs coated with organic compounds show a better combustion performance: they sacrifice ignition time but dramatically increase the combustion temperature which leads the whole ANP into a gas-phase combustion. Such improvement will enable ANPs to release more heat, obtain higher burning rate and effectively prevent nozzle blockage.